(untitled) (Contemporary Journal of Social Science Review, 2025)
Growing environmental concerns have intensified the debate over the key derivers of environmental degradation. This study contributes to that discussion by examining the impact of military expenditures (ME) on environmental degradation (ED). To address this objective, annual data for a panel of 38 high-income countries from 2000 to 2021 are utilized. Several diagnostic tests are conducted to evaluate data quality and validate model assumptions. The results support the use of second-generation panel techniques to assess stationarity and the Westerlund cointegration test to confirm the existence of a long-run relationship. Furthermore, the Panel Quantile Regression Model (PQM) is employed to investigate the hypothesized relationship and to capture distributional heterogeneity across different emission levels. The findings reveal a positive and statistically significant relationship between ME and ED across lower, middle, and upper quantiles in high-income economies. Overall, the study contributes to the limited literature on the environmental consequences of military spending and provides important policy insights for aligning national defense priorities with global climate commitments.